2007
DOI: 10.1128/aem.00592-07
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic Anoxygenic Phototrophic Bacteria Attached to Particles in Turbid Waters of the Delaware and Chesapeake Estuaries

Abstract: Aerobic anoxygenic phototrophic (AAP) bacteria are photoheterotrophs that, if abundant, may be biogeochemically important in the oceans. We used epifluorescence microscopy and quantitative PCR (qPCR) to examine the abundance of these bacteria by enumerating cells with bacteriochlorophyll a (bChl a) and the light-reaction center gene pufM, respectively. In the surface waters of the Delaware estuary, AAP bacteria were abundant, comprising up to 34% of prokaryotes, although the percentage varied greatly with loca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
84
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 89 publications
(94 citation statements)
references
References 51 publications
8
84
2
Order By: Relevance
“…Consistent with the net increase of their abundance after glucose additions in most stations, this supports the view that AAP bacteria represent a physiological group of photoheterotrophs able to use light-derived energy to rapidly grow when organic carbon sources are available. This is in agreement with their high abundances in estuarine waters (Schwalbach and Fuhrman, 2005;Waidner and Kirchman, 2007) and their common association with phytoplankton blooms (Gonzalez et al, 2000;Suzuki et al, 2001).…”
Section: Bacterial Productionsupporting
confidence: 75%
See 3 more Smart Citations
“…Consistent with the net increase of their abundance after glucose additions in most stations, this supports the view that AAP bacteria represent a physiological group of photoheterotrophs able to use light-derived energy to rapidly grow when organic carbon sources are available. This is in agreement with their high abundances in estuarine waters (Schwalbach and Fuhrman, 2005;Waidner and Kirchman, 2007) and their common association with phytoplankton blooms (Gonzalez et al, 2000;Suzuki et al, 2001).…”
Section: Bacterial Productionsupporting
confidence: 75%
“…In contrast, various reports showed that these organisms are abundant in eutrophic as well as in oligotrophic environments (Jiao et al, 2007;Koblížek et al, 2006;Yutin et al, 2007). Other authors suggested that nutrient concentrations (Mašín et al, 2008), attachment to particles Waidner and Kirchman, 2007) or light intensity (Koblížek et al, 2003;Shiba, 1991) may influence AAP bacterial abundance.…”
mentioning
confidence: 75%
See 2 more Smart Citations
“…Grossart and Simon (1993) found lake particle aggregates to be densely colonized by bacteria, with approximately 10 8 bacterial cells per mL, 100 times higher than concentrations in the bulk water. The presence of particleattached bacteria may also result in greater community diversity, as has been demonstrated in studies of estuarine mixing zones (Crump et al, 1998;Waidner and Kirchman, 2007). A study by Ploug and Grossart (2000) identified a positive correlation between bacterial production, particulate organic carbon and aggregate size.…”
mentioning
confidence: 82%